2019
DOI: 10.1029/2019ja026796
|View full text |Cite
|
Sign up to set email alerts
|

L Versus Time Structures of Dayside Magnetic Pulsations Detected by the European Quasi‐Meridional Magnetometer Array

Abstract: We studied the spatiotemporal structure of ground magnetic pulsations on the dayside by displaying magnetic field perturbations detected by the European quasi‐Meridional Magnetometer Array (EMMA) as 2‐D images in the magnetic L value versus time space, called EMMAgrams. We generated EMMAgrams from observations made on 15 August 2015, including a previously studied pulsation event associated with an interplanetary shock. In addition to signatures of field line resonance driven by a cavity mode oscillation, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
(164 reference statements)
1
6
0
Order By: Relevance
“…Large amplitude stepwise increases of the solar wind dynamic pressure (sudden impulses or sudden commencements) excite classical transient pulsations (Petrinec et al, 1996). However, Takahashi and Heilig (2019) revealed that transient pulsations are excited even in the absence of strong solar wind dynamic pressure pulses, which is true in the observations presented here. In Figures 9d and 9e, we find that B t and H exhibit similar periodicities but cannot unambiguously associate individual peaks between B t and H. This explains the low space-ground coherence shown in Figure 8.…”
Section: Relation To Magnetospheric Ulf Wavesmentioning
confidence: 39%
See 3 more Smart Citations
“…Large amplitude stepwise increases of the solar wind dynamic pressure (sudden impulses or sudden commencements) excite classical transient pulsations (Petrinec et al, 1996). However, Takahashi and Heilig (2019) revealed that transient pulsations are excited even in the absence of strong solar wind dynamic pressure pulses, which is true in the observations presented here. In Figures 9d and 9e, we find that B t and H exhibit similar periodicities but cannot unambiguously associate individual peaks between B t and H. This explains the low space-ground coherence shown in Figure 8.…”
Section: Relation To Magnetospheric Ulf Wavesmentioning
confidence: 39%
“…To gain more insight into the space-ground relationship, we generated EMMA grams (Takahashi & Heilig, 2019). EMMA grams display high-pass filtered magnetic field time series from many (23 in the present study) stations as two-dimensional (2-D) images in the time versus L space.…”
Section: Relation To Magnetospheric Ulf Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Toroidal waves are excited by driver fast mode waves through steady field line resonance (Chen & Hasegawa, 1974; Southwood, 1974) or impulsive triggering (Takahashi & Heilig, 2019). The driver waves may originate from solar wind dynamic pressure pulses (Sarris et al., 2010), foreshock ULF waves (Clausen et al., 2009), or nightside disturbances associated with substorms (Takahashi et al., 1996).…”
Section: Introductionmentioning
confidence: 99%